Effective inactivation of Saccharomyces cerevisiae in minimally processed Makgeolli using low-pressure homogenization-based pasteurization - Bak, Jin Seop (Springerplus, 2015)
In order to address the limitations associated with the inefficient pasteurization platform used to make Makgeolli, such as the presence of turbid colloidal dispersions in suspension, commercially available Makgeolli was minimally processed using a low-pressure homogenization-based pasteurization (LHBP) process. This continuous process demonstrates that promptly reducing the exposure time to excessive heat using either large molecules or insoluble particles can dramatically improve internal quality and decrease irreversible damage. Specifically, optimal homogenization increased concomitantly with physical parameters such as colloidal stability (65.0% of maximum and below 25-μm particles) following two repetitions at 25.0 MPa. However, biochemical parameters such as microbial population, acidity, and the presence of fermentable sugars rarely affected Makgeolli quality. Remarkably, there was a 4.5-log reduction in the number of Saccharomyces cerevisiae target cells at 53.5°C for 70 sec in optimally homogenized Makgeolli. This value was higher than the 37.7% measured from traditionally pasteurized Makgeolli. In contrast to the analytical similarity among homogenized Makgeollis, our objective quality evaluation demonstrated significant differences between pasteurized (or unpasteurized) Makgeolli and LHBP-treated Makgeolli. Low-pressure homogenization-based pasteurization, Makgeolli, minimal processing-preservation, Saccharomyces cerevisiae, suspension stability. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40064-015-0936-4) contains supplementary material, which is available to authorized users.